Morphoea and Borrelia burgdorferi: results from the Scottish Highlands in the context of the world literature. Issue 6 (1st December 2002) - Goodlad, J R; Davidson, M M; Gordon, P; Billington, R; Ho-Yen, D O
Abstract : Aims: Previous studies investigating the link between infection with Borrelia burgdorferi and morphoea have produced conflicting results. Often, these studies have been undertaken in patients from different regions or countries, and using methods of varying sensitivity for detecting Borrelia burgdorferi infection. This study aimed to establish whether a relation could be demonstrated in the Highlands of Scotland, an area with endemic Lyme disease, with the use of a sensitive method for detecting the organism. Methods: The study was performed on biopsies of lesional skin taken from 16 patients from the Highlands of Scotland with typical clinical features of morphoea. After histological confirmation of the diagnosis, a nested polymerase chain reaction (PCR) using primers to a unique conserved region of the Borrelia burgdorferi flagellin gene was performed on DNA extracts from each biopsy. A literature search was also performed for comparable studies. Results: None of the 16 patients had documented clinical evidence of previous infection with B burgdorferi . DNA was successfully extracted from 14 of the 16 cases but all of these were negative using PCR for B burgdorferi specific DNA, despite successful amplification of appropriate positive controls in every test. The results were compared with those of other documented studies. Conclusions: Examination of the literature suggests that there is a strong geographical relation between B burgdorferi and morphoea. These results, in which no such association was found, indicate that morphoea may not be associated with the subspecies of B burgdorferi found in the Highlands of Scotland.